2019
DOI: 10.1556/168.2019.20.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and size of birds determine the position of the species in plant-frugivore interaction networks in fragmented forests

Abstract: The relationships between frugivorous animals and plants are of vital importance particularly in tropical forests. The way species interact and how they are organized within interaction networks could be determined by their ecological and morphological characteristics. This study evaluates the hypothesis that the topological position of species within an interaction network is determined by their degree of frugivory, body size, and abundance. Thus, we constructed the frugivory network between birds and plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…While the importance of degree of frugivory on species' roles supports findings from native-dominated communities (13)(14)(15); but see ref. 20), this work also highlights the importance of species abundances, which is a well-known driver of interaction frequencies in mutualistic networks (e.g., refs. 16-21 and 23), but has been less extensively studied with respect to its impact on species' roles (but see refs.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…While the importance of degree of frugivory on species' roles supports findings from native-dominated communities (13)(14)(15); but see ref. 20), this work also highlights the importance of species abundances, which is a well-known driver of interaction frequencies in mutualistic networks (e.g., refs. 16-21 and 23), but has been less extensively studied with respect to its impact on species' roles (but see refs.…”
Section: Resultsmentioning
confidence: 63%
“…Although relative abundances, morphological, and behavioral characteristics often influence seed disperser-plant interactions, some variables that are widely known to influence mutualistic interactions have received little attention in the examination of species' roles (16)(17)(18); but see refs. [19][20][21]. Furthermore, different mechanisms may operate at distinct spatial scales (22).…”
mentioning
confidence: 99%
“…The model includes frugivore taxonomic identity as a random effect. Marginal and conditional (in parentheses) R 2 values are also shown on centrality measures (Montoya-Arango, Acevedo-Quintero, & Parra, 2019). The differential contribution of frugivores to network structure comes from variability in the frequency and identity of frugivore-plant interactions since some species have the ability to establish more partner plant relationships, or interact selectively with plants of different groups (Dehling, Jordano, Schaefer, Böhning-Gaese, & Schleuning, 2016;Olesen et al, 2011).…”
Section: Differential Role Of Frugivore Species In Network Topologymentioning
confidence: 99%
“…Here we aim to: (1) describe the structure of an avian seed dispersal network in a protected and diverse Neotropical community; (2) identify the most relevant seed dispersers in the network using several different approaches, including the recently proposed core-periphery framework; and (3) identify the main ecological determinants of the structural role of birds in the network, contrasting niche-and neutrality-based predictors. We expected to find (1) a network with high values of specialization and modularity and with a core composed of highly connected birds (Olesen et al 2007, Dugger et al 2018, due to the high richness of species in the study area (Vitorino et al 2018); (2) the degree of frugivory, representing a niche process, as the main ecological driver of species' roles in the network (Mello et al 2014, Sebasti an-Gonz alez 2017), considering the high fruit consumption rates of specialist frugivores, and their representativeness in protected and megadiverse tropical areas (Belmaker et al 2012, Dalsgaard et al 2017 ; (3) at the same time, considering the neutral-niche continuum model (see Vizentin-Bugoni et al 2018) and effects of neutrality already reported in the structuring of ecological networks (Krishna et al 2008, Machado-de-Souza et al 2019, we expected to find the abundance of birds as a predictor of species' roles with, however, less relevance in relation to niche processes, as might be expected for more intact preserved tropical areas (Montoya-Arango et al 2019).…”
mentioning
confidence: 92%
“…2019), we expected to find the abundance of birds as a predictor of species' roles with, however, less relevance in relation to niche processes, as might be expected for more intact preserved tropical areas (Montoya‐Arango et al . 2019).…”
mentioning
confidence: 99%